SELECTION OF A DECISION MODEL FOR ROLLING STOCK MAINTENANCE SCHEDULING - Asekun, Olabanji O; Fourie, Cornelius Jacobus (The South African Journal of Industrial Engineering, 2015)
Rolling stock is the most maintenance intensive part of the railway system and therefore, the most vulnerable if maintenance is neglected. It is therefore, essential to have an efficient maintenance schedule for rolling stock components. A decision support model can be used to achieve this. However, selecting the appropriate model to achieve this is vital to the success of the decision support model. In this paper a practical way of selecting the appropriate model to develop a decision support for scheduling of rolling stock maintenance, is presented. A case study is used as a numerical example for the proposed framework.